Veterinary toxicology : (Butterwoth-Heinemann, 2007)
Veterinary Toxicology is a unique single reference that teaches the basic principles of veterinary toxicology to any student at the DVM, MS or PhD level and will continue to serve as a clinical reference for practicing veterinary toxicologists, poison control centers, marine biologists, environmentalists, and animal scientists